Analisis Pengaruh Pertanian Global terhadap Pelanggaran HAM (Studi Kasus Pertanian Rumah Kaca El Ejido) - Muhammad Ficky (Jurnal Sentris, 2018)
According to the ancient Greek history, Gaia was the goddess of the earth. This concept reflected in traditional agriculture system that depends on nature and brings limitations. However, with the evolution of human’s understanding of surrounding environment and natural resources has changed the way of agriculture. The creation of The World Trade Organization (WTO) appears to achieve free market and to removing all economic boundaries among nations through the free market. Subsequently, the concept of Food Security becomes important. This brings effect in agriculture sector where all nations increase their food production in order to compete in global market. As the consequences cultural and ecological diversity are considered as obstacles and exploited to achieve economic progress that leads to poverty and hunger. On the other hand, our environment will damage and no longer sustainable for our generation in the future. Along these lines, globalization does not always refer to overall development but also threatens human security. This paper will examine how globalized agriculture threatens human security in four parts. Firstly, it will give the highlight of globalized agriculture concept along with the explanation about Gaia theory that was formulated by James E. Lovelock. Then, it will examine the condition of greenhouse farm in Almeria, Spain. Furthermore, this paper will conclude the link between globalized agriculture and human security with Gaia theory point of view. In the end, this paper will purpose a solution for sustainable agriculture.